Feasibility and safety of Reveal LINQ insertion in a sterile procedure room versus electrophysiology laboratory. (15th November 2016) - Wong, Geoffrey R.; Lau, Dennis H.; Middeldorp, Melissa E.; Harrington, Judith A.; Stolcman, Simon; Wilson, Lauren; Twomey, Darragh J.; Kumar, Sharath; Munawar, Dian A.; Khokhar, Kashif B.; Mahajan, Rajiv; Sanders, Prashanthan
Abstract: Background: Insertable cardiac monitors (ICMs) are increasingly utilized for diagnosis of unexplained syncope and arrhythmia monitoring. The Reveal LINQ is a novel miniaturized ICM with improved algorithms. The feasibility and safety of insertion outside the traditional electrophysiology laboratory is unknown. Here we compare outcomes of Reveal LINQ insertion in different environments. Methods: We report on a prospective, single-centre, non-randomized, observational experience of consecutive Reveal LINQ implantation in the electrophysiology laboratory or a procedure room between October 2013 and October 2015. Results: Of 178 consecutive patients who underwent LINQ device insertion, 80 were implanted in the electrophysiology laboratory and 98 in a procedure room. There were no significant differences in baseline patient characteristics. All implants were performed in the recommended manufacturer method with the exception of 1 which required suture closure. Only a minority received peri-procedural antibiotics with a greater number in the electrophysiology laboratory group (11 [14%] versus 1 [1%], p = 0.007). Overall, there were 3 (1.7%) complications with no significant difference between the electrophysiology laboratory and the procedure room groups (2 [3%] versus 1 [1%], p = 0.45). There was 1 superficial infection in the procedure room group and 1 superficial infection with device extrusion and 1 traumatic extrusion in the electrophysiology laboratory group. Procedure room implantation subjectively improved laboratory efficiency and patient flow. Conclusion: Reveal LINQ insertion can be safely performed outside of the cardiac laboratory provided a sterile technique is followed by the operator using manufacturer recommendations for insertion. These findings have significant resource implications for hospitals undertaking such procedures.